Effectiveness of Steroid and Non-Steroid Mouthwashes for Oral Lichen Planus: A Systematic Review - Purnomo, Luthfiyyah Andini; Zakiawati, Dewi; Nur'aeny, Nanan (Universitas Baiturrahmah, 2025)
Definitive management of Oral lichen planus (OLP) remains challenging due to its intractable nature and unclear cause. Steroid and non-steroid mouthwash preparations are recommended for OLP, especially for diffuse or difficult-to-access lesions. This review aims to evaluate the efficacy of available steroid and non-steroid anti-inflammatory mouthwashes in managing OLP focusing on pain reduction, lesion size reduction, and possible side effects. A systematic literature search from 2012- 2022 was conducted using Scopus, PubMed, and ScienceDirect, following PRISMA guidelines. Nine RCTs included with steroid mouthwashes (dexamethasone, triamcinolone) show promise as effective treatment options for reducing pain and lesion size in OLP, while non-steroid mouthwash (cyclosporine) demonstrates better long-term remission. Natural adjuvant therapies, like nanocurcumin gel, quercetin capsules, and SE-ACE tablets can support the use of steroid mouthwashes. Additionally, fluconazole capsule, itraconazole capsule, and nystatin suspension can be used as adjuvant therapy to prevent secondary candidiasis infection caused by steroid mouthwashes. The risk assessment of bias using the Joanna Briggs Institute (JBI) Critical Appraisal Tools showed seven articles with a low risk of bias and two with a moderate risk. However, heterogeneity in the type, dose, trial duration, and outcome measures limit direct comparisons of treatment effectiveness.